Development of Online Learning Media using Guided Inquiry to Improve Science Process Skills of Elementary School Students Assisted by Microsoft Office 365 - Siti Ulfayantik; Budi Jatmiko; Zainul Arifin Imam Supardi (Universitas Negeri Surabaya, 2022)
The research aims to produce a valid, practical, and effective Microsoft Office 365 guided inquiry learning tool to practice students' science process skills in elementary school. The development of this learning device uses a Four-D model. It is tested on students at Elementary School, in grade IV, class A and B using the design of one Group Pretest-Posttest design. The learning devices developed include syllabus, lesson plans, teaching materials, student worksheets, and science process skills tests with teaching materials themed light properties. Data collection uses validation, observation, and test methods—data analysis techniques using N-Gain, Paired samples t-test, and independent t-test. Science process skill results increased by an average N-Gain of more than 75% or categorized high. The data analysis techniques used to determine the improvement of science process skills are by using Paired samples t-Test that there is an increase in the scientific process skills in the grade IV Elementary School after learning activities. The independent t-test showed that the learning devices used in the sample group had a relatively similar (consistent) influence. Based on data analysis, it can be concluded that the guided inquiry model online science learning device effectively improves the science process skills of elementary school students. This study implies that Microsoft Office 365-assisted online science learning tools have the potential to be a solution and alternative to improve science process skills.